Linguistic conceptualization of pride in Russian and English cultures - Vladimir Ilyich Karasik (Russian Language Studies, 2018)
The paper deals with linguistic conceptualization of pride in Russian and English. Main notional vectors of such mental entity are specified. This concept is represented as a semantic field of affiliated meanings defining various aspects of personal social status evaluation. I argue that exaggerated selfrepresentation is expressed as contempt to the others, desire to dominate and show disrespect to other people, and to show them that they belong to a lower class. This concept is often illustrated by metaphors of size and height. Common ways of nonverbal demonstration of pride are certain facial expressions and gestures. Typical objects of feeling proud of are described. Everyday and religious discourse substantially varies in expression and evaluation of pride. Proverbs focus on critical evaluation of being too proud of oneself, whereas aphorisms show an ambivalent attitude to this concept.